The Radical Feminism Revealed in The Novel The Scarlet Letter and The Impact Of Radical Vews In Relation to Today’s Life - Mokalu, Feronika Angelina; Mamentu, Agustine C.; Posumah, Jeni (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
The Radical Feminism revealed in the Novel The Scarlet Letter and the Impacts of Radical Vews in Relation to Today’s Life. FERONIKA ANGELINA MOKALU, AGUSTINE C. MAMENTU, JENNIE POSUMAH Universitas Negeri Manado Abstract : Background of the Problem: The novel "The Scarlet Letter" by Nathaniel Hawthorne, published in 1850, depicts issues of gender and morality that are relevant today. The concept of radical feminism that appears in this text invites readers to understand patriarchal structures and the role of women in society.Research Objectives: This research aims to examine how radical feminism is expressed in "The Scarlet Letter" and to analyze the impact of this radical view on contemporary life, especially in the context of the struggle for women’s rights. Research Method: This research uses a qualitative approach with literary text analysis. Data was collected through in-depth exploration of the novel, followed by a review of literature on feminism and relevant social theories. Research Results: The results of the analysis show that the character of Hester Prynne reflects resistance to patriarchal norms, showing how the emphasis on women’s autonomy can be connected to the current feminist movement. This research also identifies the relevance of these radical views in modern issues, such as gender equality and social stigma. Keywords: Radical feminism, The Scarlet Letter, Hester Prynne, patriarchy, women’s rights, literary analysis.